Impacts of population growth, economic development, and technical change on global food production and consumption - Schneider, Uwe; Havlík, Petr; Schmid, Erwin; Valin, Hugo; Mosnier, Aline; Obersteiner, Michael; Böttcher, Hannes; Skalsky, Rastislav; Balkovič, Juraj; Sauer, Timm; Fritz, Steffen (Elsevier, 2011)
Over the next decades mankind will demand more food from fewer land and water resources. This study quantifies the food production impacts of four alternative development scenarios from the Millennium Ecosystem Assessment and the Special Report on Emission Scenarios. Partially and jointly considered are land and water supply impacts from population growth, and technical change, as well as forest and agricultural commodity demand shifts from population growth and economic development. The income impacts on food demand are computed with dynamic elasticities. Simulations with a global, partial equilibrium model of the agricultural and forest sectors show that per capita food levels increase in all examined development scenarios with minor impacts on food prices. Global agricultural land increases by up to 14% between 2010 and 2030. Deforestation restrictions strongly impact the price of land and water resources but have little consequences for the global level of food production and food prices. While projected income changes have the highest partial impact on per capita food consumption levels, population growth leads to the highest increase in total food production. The impact of technical change is amplified or mitigated by adaptations of land management intensities.